THE PRACTICE OF USING HOUSEHOLD SURVEYS FOR ESTIMATING UNDECLARED EMIGRATION - Kasnauskienė, Gindra; Igoševa, Rima (Ekonomika, 2010)
In the modern world of globalization, emigration has become one of the most vital events that should be reflected in the population statistics due to its impact on the size and structure of the country’s population. The importance of correct evaluation of emigration is very high because, by influencing the efficiency of government policy making, it can help to avoid the negative consequences of emigration. However, many national statistical institutions of different countries fail to provide accurate statistics on emigration because of various obstacles which arise in the usage of administrative data sources. Politicians, researchers and experts engaged in the analysis of demographic development and the migration phenomenon are especially not satisfied with the amount and quality of the current statistical information provided by the official statistics. One of the important tasks for every NSI is not only to reflect the stocks and flows of emigrants, but also to provide their demographic and socioeconomic characteristics for the in-depth analysis of the determinants and consequences of emigration. Unfortunately, administrative data sources are usually unable to provide reliable statistics on the volume of undeclared emigration as well as on the characteristics of emigrants. Thus, the article discusses the benefits of conducting household surveys for obtaining information about characteristics of emigrants and filling this gap. p>